Konsep Berpikir dan Dzikir sebagai Proses Pendidikan Islam - Kurnia, Asep; Ahmad EQ, Nurwadjah; Suhartini, Andewi (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2021)
This research aims to examine the concept of thinking and dhikr as the process of Islamic education by using the method of literature or library research, namely research conducted through data collection or scientific papers with research objects or data collection is literature. The results of the analysis showed that, the concept of Thinking and dhikr are two activities that should not be separated. By intermediaries thinking about the universe, then comes memory as the conclusion of thinking, namely that all this does not happen by itself, but there is a God almighty creator, that is Allah SWT. Because of the real thinking, remember the more real. Islamic education is expected to change the behavior of learners, increase the knowledge of learners by channeling or transferring the concept of science and able to improve good ethics. In short, Islamic education should be able to print the ideal Muslim person as caliph.